Allergy and sensitization during childhood associated with prenatal and lactational exposure to marine pollutants - Grandjean, Philippe; Poulsen, Lars Kærgaard; Heilmann, Carsten; Steuerwald, Ulrike; Weihe, Pál (Environmental Health Perspectives, 2010)
BACKGROUND: Breast-feeding may affect the risk of developing allergy during childhood and may also cause exposure to immunotoxicants, such as polychlorinated biphenyls (PCBs), which are of concern as marine pollutants in the Faroe Islands and the Arctic region. OBJECTIVES: The objective was to assess whether sensitization and development of allergic disease is associated with duration of breast-feeding and prenatal or postnatal exposures to PCBs and methylmercury. METHODS: A cohort of 656 singleton births was formed in the Faroe Islands during 1999-2001. Duration of breast-feeding and history of asthma and atopic dermatitis were recorded at clinical examinations at 5 and 7 years of age. PCB and mercury concentrations were determined in blood samples obtained at parturition and at follow-up. Serum from 464 children (71%) at 7 years of age was analyzed for total immunoglobulin E (IgE) and grass-specific IgE. RESULTS: The total IgE concentration in serum at 7 years of age was positively associated both with the concomitant serum PCB concentration and with the duration of breast-feeding. However, the effect only of the latter was substantially attenuated in a multivariate analysis. A raised grass-specific IgE concentration compatible with sensitization was positively associated with the duration of breast-feeding and inversely associated with prenatal methylmercury exposure. However, a history of asthma or atopic dermatitis was not associated with the duration of breast-feeding, although children with atopic dermatitis had lower prenatal PCB exposures than did nonallergic children. CONCLUSIONS: These findings suggest that developmental exposure to immunotoxicants may both increase and decrease the risk of allergic disease and that associations between breast-feeding and subsequent allergic disease in children may, at least in part, reflect lactational exposure to immunotoxic food contaminants.